Evaluation of social and psychological impacts on leprosy treatment: A longitudinal study (Research, Society and Development, 2024)
Leprosy, also known as "leprosy," has ancient roots and is caused by the bacteria Mycobacterium leprae. Despite being an ancient disease, leprosy is still a public health problem in Brazil. The history of leprosy in the country is marked by compulsory isolation in leprosariums. This disease is infectious and contagious, mainly affecting the peripheral nerves, resulting in several disabilities. It manifests itself in several ways and can be transmitted through contact with untreated patients or through respiratory secretions. The diagnosis is made clinically, and treatment involves polychemotherapy, including Rifampicin, Dapsone and Clofazimine. Medications can cause side effects such as skin rashes. The National Leprosy Control Plan (PNCH) aims to expand early diagnosis and treatment, reducing disabilities and transmission. This study is based on nursing consultations, collecting data from patients who completed treatment. The assistance of the nursing team is important in treating patients with leprosy, describing the clinical and epidemiological characteristics of patients diagnosed with leprosy. Leprosy is a global public health concern, with high prevalence rates in countries such as India, Brazil and Indonesia. Clinical forms range from tuberculoid to lepromatous, with indeterminate leprosy as the initial form.